ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETENSI KARYAWAN PADA KANTOR CABANG BANK CENTRAL ASIA - Surya Hardi Lukita; Ahmad Hidayat Sutawijaya; Siti Mariam; Abdul Haeba Ramli (POLITEKNIK LP3I JAKARTA, 2025)
In this era of globalization and intense competition in the business world, retaining qualified and potential employees is an important challenge for many companies, especially banks. However, a high employee turnover rate is one of the main problems that companies often face. BCA as one of the banks that is able to maintain employee retention well, therefore, analyzing factors such as Job Satisfaction, Compensation, Company Culture and Career Development Opportunities which are thought to influence Employee Retention at BCA bank branch offices is important. The research approach used in this research is quantitative research using SPSS software. The population in this study were employees at BCA bank branch offices with the criteria of having permanent employee status, working for more than or equal to three years and domiciled at BCA bank branch offices in JABODETABEK. Determining respondents used a non-probability sampling method with a total of 130 respondents. The results of this research showed that the variables Job Satisfaction, Compensation, Company Culture and Career Development Opportunities simultaneously had a positive effect on Employee Retention at BCA bank branch offices in JABODETABEK. Then it was also found that the results of this research partially showed that Job Satisfaction and Company Culture did not have a positive effect on Employee Retention at BCA bank branch offices in JABODETABEK. Compensation and Career Development Opportunities have a positive effect on Employee Retention at BCA bank branch offices in JABODETABEK.